2010
DOI: 10.1155/2010/635912
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARsα,β/δ, andγImpairs TGF-β1-Induced Collagens' Production and Modulat

Abstract: Background and Purpose. We investigated the potency of Peroxisome Proliferators-Activated Receptors (PPARs) α, β/δ, and γ agonists to modulate Transforming Growth Factor-β1 (TGF-β1-) induced collagen production or changes in Tissue Inhibitor of Matrix Metalloproteinase- (TIMP-) 1/Matrix Metalloproteinase (MMP) balance in rat chondrocytes embedded in alginate beads. Experimental Approach. Collagen production was evaluated by quantitative Sirius red staining, while TIMP-1 protein levels and global MMP (-1, -2, -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…TZDs also inhibit NFassociated downstream COX-2 and iNOS signaling in osteoblasts, and thus might improve the inflammatory environment at ossification sites [254]. Recent findings show that extracellular matrix production by chondrocytes is controlled not only by PPAR but also by PPAR and PPAR / [255]. In an experimental model of rheumatoid arthritis, administration of the PPAR ligand fenofibrate reduces skeletal muscle wasting, thus alleviating the external symptoms of arthritis [256].…”
Section: Potential Use Of Ppar Ligands In Arthritis Treatment: Pros Amentioning
confidence: 99%
“…TZDs also inhibit NFassociated downstream COX-2 and iNOS signaling in osteoblasts, and thus might improve the inflammatory environment at ossification sites [254]. Recent findings show that extracellular matrix production by chondrocytes is controlled not only by PPAR but also by PPAR and PPAR / [255]. In an experimental model of rheumatoid arthritis, administration of the PPAR ligand fenofibrate reduces skeletal muscle wasting, thus alleviating the external symptoms of arthritis [256].…”
Section: Potential Use Of Ppar Ligands In Arthritis Treatment: Pros Amentioning
confidence: 99%
“…Cell proliferation was assessed aer 7, 14 and 21 days of hMSCs culture onto the lms using the Hoechst assay, which allows cell DNA quantication. 55 Hoechst 33258 is a uorescent dye which binds to DNA allowing its quantication. Briey, hMSCs were harvested from 12-well plates coated with the lms.…”
Section: 6mentioning
confidence: 99%
“…Cell metabolic activity. Cell metabolic activity was measured using the MTT assay as described explained elsewhere, 55 where hMSCs seeded on standard plastic 96-well culture plates was used as reference value to normalize the results.…”
Section: 6mentioning
confidence: 99%
“…PPAR γ is expressed in dermal fibroblasts and PPAR γ agonists, such as troglitazone, suppress the biosynthesis of matrix materials, such as collagen I or fibronectin, by inhibiting transforming growth factor (TGF)-β, a major factor in fibrosis [15]. Rosiglitazone (PPAR γ agonist) increases the expression of matrix metalloproteinase (MMP)-3 and MMP-13, while it decreases the expression of tissue inhibitor of metalloprotease (TIMP)-1 [16]. Furthermore, it was reported that 5,7-dimethoxyflavone, an activator of PPAR α/γ, not only inhibits the increase in MMP-1, MMP-2, MMP-9, and ROS induced by UV light in fibroblasts, but also suppresses inflammatory cytokines, such as interleukin (IL)-6 and IL-8 [17].…”
Section: Introductionmentioning
confidence: 99%